Control Interno de Costos y Gastos de la Asociación Asotexmaben - Macías Ortega, Claudio Erick (2018)
The Association Asotexmaben is located in the city of Babahoyo having the same three years of operation, subject to the superintendence of the popular and solidarity economy, its main activity is the textile activity, it has 11 active members, and its main clients are the entities of the public sector. The internal control of costs and expenses is a procedure that is in charge of a good balance of the same, avoiding that they are very high or diminished to the point that cause certain factors that are affecting the turn of the company. Direct and indirect raw materials are costs that are incurred for the production process, reason that must be planned, in order to avoid other costs, and at the end of a period to have low profit margins. The association Asotexmaben has at the end of a productive process a large amount of direct and indirect waste of raw materials, raising costs and reducing profit, this point does not affect the sale price since the contracts that are executed are at a specific amount. In the winery at the end of a production process is raw material, a question that if acquired is to be used in the production process and not be stored in the warehouse, having the amount of raw material to be used. The spinning contract is a contract that the Association performs the day before the beginning of class in the Costa Régime, producing uniform in mass, the space of the production plant is not prepared for said contract, manifested by the members themselves declaring the discomfort that exists at the time of production. The lack of planning of the amounts of raw material to be used is vital for the production process, in the association said activity is not efficiently carried out, having costs for other expenditures at the time of making more acquisitors. The management of expenses is key to not incur many in them, or in order not to have to compromise other points in the production process, the Association in this period of spinning understood that the expenses meet an objective and that to treat them we must analyze all the possible extremes. During this period, Hilando's contract was delayed due to economic reasons. The research source this data in its financial statements. Información del Traductor de GoogleComunidadMóvilAcerca de GooglePrivacidad y condicionesAyudaEnviar comentarios